Pengembangan Konvergensi Media Berbasis Website Company Profile â€œSwacreativeâ€ - Pradhani, Anindya Rahma Putri; Astuti, Aprilina Dwi; Kristiadi, David (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
Companies need to present their identities, services, products and works to the public, using company profile websites. Some media can be converged into a company profile website to inform complete company information in an interesting way. However, in developing media convergence for company profiles based on websites, there are still many websites that have not implemented usability yet, so users face difficulties to get the information. Therefore, the development of a media convergence based on company profile website "Swacreative", implements the principle of usability with aspects of learnability and efficiency. Learnability and efficiency are applied to content layout, text types and colors, navigation features, photo and video display options. Usability testing was followed by 41 respondents. The test result shows that the website met the learnability and efficiency aspects. Majority of respondents agree that the website was easy to understand and to learn, the website's interactions were clear and easy to understand, the website's pages appeared without errors, the website's text types and colors were clearly readable and the website’s menu structures were easy to understand. Meanwhile, about the efficiency aspect of the website, the majority of respondents agree that the menus were displayed fast, navigation options were available, content design was structured, photo and video display options were available, and the website was able to be accessed using a multi web browser.